Potential management opportunities for cow/calf producers to maximize profit - Harborth, Karl Walter (Kansas State University, 2006)
The primary study investigated the use of ractopamine HCl and implants in cull beef cows. Thirty-two cull cows were used to determine the effects of feeding ractopamine HCl and/or implanting on feedlot performance and carcass composition. Cows were individually fed a high concentrate diet for 60 days. Carcass data were collected and carcasses were fabricated. Implanted cows had greater dressing percentages and tended to have heavier hot carcass weights than non-implanted cows. Cows that had been treated with implant and ractopamine HCl tended to be fatter than those not treated. Ractopamine HCl fed cows had more marbling than their contemporaries. The data also indicated that younger cows (< 6 years of age) had greater feedlot performance than the older cows. An experiment was conducted to determine if corn and grain sorghum dried distillers grains could be effective protein supplements for growing cattle. Crossbred heifers (n = 78) were individually fed 2.72 kg·head·-1d·-1 of supplements containing corn, soybean meal, and grain sorghum; or cracked corn and corn distillers grains with solubles; or cracked corn, sorghum distillers grains with solubles, and ground grain sorghum (all formulated to equal 20% CP). Heifers grazed native-grass and were fed smooth broom hay. A digestion trial was done during the last week of the trial. No differences were noted in weight gain or total diet digestibility, however, DMI was less for heifers receiving either distiller’s based supplement. Ninety-six pregnant, mature, spring-calving cows grazing native grass pasture were used to determine if early weaning calves reduced subsequent winter supplementation cost. Previous to the feeding trial, calves had been weaned at 115 or 212 d of age. Cows were fed either 1.4 kg·hd-1·d-1 or 1.27 kg·hd-1·d-1 of a common 45% CP supplement. Cows were supplemented for an average of 110 d of pregnancy. Earlyweaned cows were heavier and had greater body condition scores than contemporaries at the commencement of supplementation. At calving the early-weaned cows fed the lesser supplemental amount had similar body weight and body condition scores as later-weaned cows fed the greater amount of supplement, thus, the early weaning routine allowed a 30% savings of winter protein supplement.
Keywords: Ractopamine; Cull cows; Agriculture, Animal Culture and Nutrition (0475)